Impact of entrepreneur's commitment on entrepreneurial coaching relationship - Fitouri Mohamed; Samia Karoui Zouaoui (Cogent Business & Management, 2021)
The purpose of the study is the influence of the entrepreneur commitment on the success of the entrepreneur-coach relationship. The data were gathered from 350 novice entrepreneur's. The data were analyzed with structural equation modeling.The findings suggest that the success of the entrepreneur-coach relationship is conditioned by the entrepreneur Commitment. Based on the results, for entrepreneurs, it is very useful to know how to manage this relationship. It must understand the importance of psychological determinants in the success of their accompanying relationship. It must also recognise the importance of interaction between the different partners involved in the relationship. This knowledge can help accompaniments raise a share of unknown in the failures of newly created companies despite their accompaniment. Our work contributes to a more precise and concrete knowledge of the entrepreneurial accompaniment relationship which is beyond the level of commitment of the novice entrepreneur.
Keywords: 650; commitment; Coaching- relationship-; Entrepreneur